(untitled) (Annual of the Faculty of Philosophy in Skopje, 2015)
This summary makes analyses of the significance and value of the archive material within the family and personal funds, for historical researches, using the exemplar of the archive material of the “Branišlav Rusić" fund, which is kept in the archive of the Macedonian Academy of Sciences and Arts. In this archive, there are records of his researches that have been carried out in the second half of the fourth and first half of the fifth decade of the 20th century in various regions of Macedonia: Ohrid- Struga Region, Prespa, Železnik (Demir Hisar), Pijanec, Delčevo-Osogovo, Slaviste, Župa, Debarsko Pole and other regions. Besides the fact that the archive material contains enormous ethnological value, the documentation referring to terrain researches made by Rusić presents a perfect historical source which may be used for studying the demographic and ethnic changes, for the migrations, for the history of the everyday life in the Macedonian villages, etc. Also, the value of Rusić’s researches lays in their comparability with other researches.